2017
DOI: 10.2337/db16-1035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RUNX1 as a Mediator of Aberrant Retinal Angiogenesis

Abstract: Proliferative diabetic retinopathy (PDR) is a common cause of blindness in the developed world’s working adult population and affects those with type 1 and type 2 diabetes. We identified Runt-related transcription factor 1 (RUNX1) as a gene upregulated in CD31+ vascular endothelial cells obtained from human PDR fibrovascular membranes (FVMs) via transcriptomic analysis. In vitro studies using human retinal microvascular endothelial cells (HRMECs) showed increased RUNX1 RNA and protein expression in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 28 publications
4
68
0
Order By: Relevance
“…Some reports show that the inhibition of RUNX1 activity results in the reduction of neovascular tufts in retinopathy [24], suggesting that RUNX1 has a close relationship with angiogenesis. Hence, we constructed DR model to investigate the expression level of RUNX1 and level of angiogenesis.…”
Section: Runx1 Was Highly Expressed In Diabetic Retinopathymentioning
confidence: 99%
“…Some reports show that the inhibition of RUNX1 activity results in the reduction of neovascular tufts in retinopathy [24], suggesting that RUNX1 has a close relationship with angiogenesis. Hence, we constructed DR model to investigate the expression level of RUNX1 and level of angiogenesis.…”
Section: Runx1 Was Highly Expressed In Diabetic Retinopathymentioning
confidence: 99%
“…Therefore, the cause of increased vascular permeability in DM remains to be further studied. As an endothelial cell marker, CD31 has been widely used to study aberrant angiogenesis in the eye . Immunohistochemistry (IHC) analysis using anti‐CD31 antibody indicated increases of vascular area in the retina of the DM mice (Figure A).…”
Section: Discussionmentioning
confidence: 66%
“…Neovascularization is a pathological feature of PDR. CD31 has been widely used as an endothelial cell marker to study the aberrant angiogenesis in the eye . Herein, we evaluated angiogenesis using CD31 staining of retinas in DM mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that CAMs are important in the development of DR (Khalfaoui et al, 2009;Ugurlu et al, 2013 of insulin and is associated with DR neovascularization (Qin, Zhang, & Xu, 2015;Sasore, Reynolds, & Kennedy, 2014). Compared with the results of transcriptomic analysis which use CD31+ vascular endothelial cells obtained from human PDR fibrovascular membranes (FVM) (Lam et al, 2017), we found the gene Col3a1 were both significantly changed, and according to the GO enrichment analysis of two researches, Col3a1 may belong to blood vessel development term (GO:0001568), suggested that Col3a1 may play a role in DR neovascularization. We also found that the positive regulation of immune system process term (GO: 0002684) was both significantly enriched in two researches.…”
Section: Discussionmentioning
confidence: 99%